Efficacy and Safety of Intravitreal Fluocinolone Acetonide Implant for Chronic Diabetic Macular Edema Previously Treated in Real-Life Practice: The REALFAc Study - Thibaud Mathis; Maxence Papegaey; Cécile Ricard; Amina Rezkallah; Frédéric Matonti; Aditya Sudhalkar; Cristina Vartin; Corinne Dot; Laurent Kodjikian (MDPI AG, 2022)
Diabetic macular edema (DME) is the main cause of visual impairment in diabetic patients and a chronic disease requiring long-term treatments. The fluocinolone acetonide (FAc) implant has recently been approved to treat DME in patients considered insufficiently responsive to available therapies. This study evaluates the functional and anatomical efficacy of the FAc implant in real-life practice. A total of 62 eyes with chronic DME were included and followed for a mean of 13.9 (+7.5) months. Previous treatment included at least anti-vascular endothelial growth factor (VEGF) in 83.9% of eyes, dexamethasone implant (DEX-I) in 100% of eyes, vitrectomy in 29.0% of eyes, and laser photocoagulation (either panretinal or focal photocoagulation) in 75.8% of eyes. The mean baseline best corrected visual acuity (BCVA) was 64.0 (+/−17.2) letters (median: 67.5 letters) with a mean DME duration of 60.3 (+/−30.6) months. The maximum BCVA gain occurred at 21 months with a mean gain of 5.0 (+/−12.7) letters. A total of 50.0% of eyes gained ≥5 letters during follow-up. Patients with lower BCVA at baseline had the lowest final BCVA (p < 0.001) but the highest BCVA gain (p = 0.02). The best overall improvement in mean central macular thickness (CMT) occurred at 18 months (p < 0.0001). The improvement in BCVA was inversely associated with the decrease in CMT and showed a decrease when CMT increased (DME recurrence). According to the history of vitrectomy, we did not find any significant difference in mean final BCVA (p = 0.1) and mean BCVA gain (p = 0.2) between eyes previously vitrectomized or not. A total of 23 eyes (37.1%) required additional treatment for DME, and 17.7% required an IOP-lowering procedure during follow-up. In conclusion, this real-life observational study demonstrated the efficacy and safety of the FAc implant in patients with chronic DME already treated with other available therapies.